The Influence of Economic Growth, Unemployment, and Capital Expenditure in East Nusa Tenggara Province - Najma Afifa Hartania; Retno Febriyastuti Widyawati (Pattimura Proceeding, 2026)
East Nusa Tenggara Province is the third poorest province in Indonesia. This study aims to analyze the effect of macroeconomic variables on the poverty rate in East Nusa Tenggara Province for the period 2017- 2023. East Nusa Tenggara Province is the third poorest province in Indonesia. Gross Regional Domestic Product (GRDP) per capita, open unemployment rate, and capital expenditure are the independent variables used in this study. This study uses panel data regression analysis using a random effects model (REM) with secondary data from 22 Districts/Cities in East Nusa Tenggara Province obtained from the Central Statistics Agency (BPS). According to this study, GRDP per capita has a significant negative effect, the Open Unemployment Rate variable has a positive and significant effect, while the capital expenditure variable has a positive and insignificant effect. Policy makers can learn a lot from this study, such as the importance of increasing economic growth and improving the quality of human resources, as well as how to optimize the capital expenditure budget for public investment in order to combat poverty effectively